The Impact of Climate Change on Food Security in KPK, Pakistan an Analysis - Sher Akbar (Social Science Review Archives, 2025)
This research investigates the effects of climate changes on food production and accessibility, particularly for the country's most vulnerable populations. Additionally, the study explores potential adaptation and mitigation strategies, such as implementing climate-resistant agricultural methods, water management, and policy reforms, to ensure food security to deal with climate change. Pakistan, a country with a fast-growing population and inadequate arable land, is experiencing many challenges in preserving food security due to the mounting threats of climate change. As a country extremely susceptible to the effects of global warming, it faces significant threats due to fluctuations in temperature, precipitation patterns, and extreme weather events. These factors directly impact agricultural productivity, the availability of water, and livestock health. The research is qualitative in nature because it helps to explain comprehensively and supports interpretive goals. Qualitative research methods are applied for data collection since the nature of the research is qualitative. The data source is secondary in nature. The findings emphasize the need for immediate action for inclusive and cohesive approaches to address the complex problem of climate change and its implications for Pakistan's food security. To face the challenges of climate change adaptation of sustainable land management, decentralized renewable systems of energy and Insurance System for crop are recommended.